Distinct factors predict use of active learning techniques by pre-tenure and tenured STEM faculty. Issue 4 (2nd October 2021) - Indorf, Jane L.; Benabentos, Rocio; Daubenmire, Patrick; Murasko, Donna; Hazari, Zahra; Potvin, Geoff; Kramer, Laird; Marsteller, Pat; Thompson, Katerina V.; Cassone, Vincent M.; Stanford, Jennifer S.
Abstract: Despite decades of research indicating that active learning techniques (ALTs) are more effective than traditional lecture, ALTs are not widely implemented in STEM undergraduate classrooms. While ALT implementation is happening in a number of disciplines, including the geosciences, most STEM teaching remains lecture-based. Understanding the contexts that correlate with ALT adoption may allow expanded implementation. ALT use was documented among STEM pre-tenure and tenured faculty respondents across 66 research-intensive, U.S. universities, using the Change in Implementation of Pedagogical Practices survey. Personal, professional, and institutional/departmental factors were analyzed for association with ALT use. Most respondents reported using some ALTs in their teaching, with no significant distinctions between pre-tenure and tenured faculty. Teaching was perceived to carry less weight in practice (e.g., in tenure and promotion decisions) than the theoretical value stated by institutions (e.g., in faculty assignments and hiring). ALT use among tenured faculty was predicted by number of recent publications, their knowledge of education initiatives, and receiving informal feedback on their teaching. ALT use among pre-tenure faculty was predicted by the number of STEM education talks given. Perception of obstacles was a negative predictor of ALT use among tenured faculty only, though both pre-tenure and tenured faculty identified barriers to ALT use. Considering these identified barriers and how to remove them could potentially increase ALT use. The findings that ALT use by tenured faculty was predicted by number of recent publications and that grant funding was neither a positive nor negative predictor of ALT use suggest that ALT use does not hinder faculty research productivity.